2017
DOI: 10.1007/s12275-017-6474-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the oral microflora of preschool children

Abstract: The oral cavity is one of the most important and complicated habitats in our body and supports diverse microbial communities. In this study, we aimed to determine the bacterial diversity and composition of various oral micro-niches. Samples were collected from supragingival plaque, saliva, and tongue coating from 10 preschool children (30 samples total). 16S rRNA gene pyrosequencing dataset generated 314,639 clean reads with an average of 10,488 ± 2,787 reads per sample. The phyla Firmicutes, Proteobacteria, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 34 publications
12
22
0
Order By: Relevance
“…While core microbiota have been shown for individual oral niches in the human literature, the genus level assignments generally differ to those observed here. On a global level, Capnocytophaga, Neisseria, Porphyromonas and Fusobacterium were observed amongst the core microbiota here, and also represent some of the genera which have been reported amongst humans [15,16]. Furthermore, several species of these genera have been shown to be abundant amongst early (24 and 48 h) canine supragingival plaque biofilm [10].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…While core microbiota have been shown for individual oral niches in the human literature, the genus level assignments generally differ to those observed here. On a global level, Capnocytophaga, Neisseria, Porphyromonas and Fusobacterium were observed amongst the core microbiota here, and also represent some of the genera which have been reported amongst humans [15,16]. Furthermore, several species of these genera have been shown to be abundant amongst early (24 and 48 h) canine supragingival plaque biofilm [10].…”
Section: Discussionsupporting
confidence: 57%
“…Human studies have indicated subsets of microbiota are core to the health of the oral cavity of different individuals, variation in microbial profiles and diversity across different oral locations and stability in microbiota over time [13][14][15][16][17]. To the best of our knowledge, an extensive study of individual canine oral niches from a microbial perspective has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies showed that a relationship exists between oral microbiome and periodontal diseases among various age groups [28][29][30][31]. However, few cohort studies have investigated the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…The samples with the A260: A280 ratios at 1.8:2.0, and the DNA concentrations in 20-100 ng/µl were screened, and the results indicated that the genomic DNA extracted met the requirements for subsequent sequencing [18]. Finally, after screening 40 high-quality samples [13,19]were selected to perform sequencing analysis: SN (caries-free saliva group, n=10); PN (caries-free plaque group, n=10); SH (caries-active saliva group, n=10); and PH (caries-active plaque group, n=10). The DNA samples were stored at −20°C before use.…”
Section: Dna Extraction and Puri Cationmentioning
confidence: 99%
“…Thanks to recent advancements in molecular biology techniques, metagenomic and metaproteomic can be used to obtain a complete analysis of the oral bacteria and proteomic. Next-generation sequencing technologies have been successfully applied in oral microbial analysis [12][13][14]. The isobaric tags for relative and absolute quantitation (iTRAQ) is a new technique which uses isotopes to label polypeptides for comparing proteomes quantitatively [15,16].…”
Section: Introductionmentioning
confidence: 99%